Bioactives from citrus food waste: types, extraction technologies and application - A. N. Anoopkumar
The Citrus fruits belong to the category where the groups of fruits are recognized to be an admirable repository of bioactive elements and phytochemical constituents, with strong biological potentials. The prominent use of Citrus fruits for nutrition as well as food processing has led to the release of a large amount of waste into the environment and surrounding, and it simultaneously burdens the nature and existence of many organisms including the human population. In order to rectify such consequences, the reuse of food waste from citrus for various advantageous effects. In this regard, the first part of the article primarily focussed on the various strategies available for the extraction of chemical elements from citrus waste and the remaining strand of the article focussed on the various bioactive compounds with special reference to their pharmacological as well as the medicinal benefits and future prospects.